A high-fat diet changes the interaction of the extracellular matrix, cytokines, and growth factors in gastric ulcer repair - Ohara, Rie [UNESP]; Dario, Felipe Lima [UNESP]; Emilio Silva, Maycon Tavares [UNESP]; Assunção, Renata [UNESP]; Rodrigues, Vinícius Peixoto [UNESP]; Bueno, Gabriela [UNESP]; Raimundo, Priscila Romano [UNESP]; Justulin, Luis Antonio [UNESP]; da Rocha, Lúcia Regina Machado [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (Elsevier, 2025)
Background: Obesity is characterized by persistent low-grade inflammation that alters the gastrointestinal system and healing process. The link between obesity and the prevalence of stomach ulcers has not yet been fully established. Aims: We investigated the healing features of gastric lesions in male Swiss mice fed a standard diet (SD) or high-fat diet (HFD) using morphometric, biochemical, and molecular parameters. Methods: After 12 weeks on different diets, the animals underwent acetic acid-induced stomach ulcer surgery. To evaluate healing patterns, the stomachs of the animals were studied at five post-induction times, including the early, middle, and late phases of healing (1, 3, 7, 10, and 14 days). Morphometric features, activity of matrix metalloproteinases 2 and 9 (MMP-2 and 9), and measurement of inflammatory and growth factors were investigated using multiplex immunoassays. Results: Compared with the SD group, the HFD group demonstrated slowing of the early healing process. During the initial phase of the healing process, the SD group had significantly higher levels of EGF, VEGF-A, and VEGF-D than the HFD group. In the intermediate phase, only the SD group showed a 70 % increase in the regeneration area compared with the initial phase of the procedure. In this phase, the SD group also had higher levels of MMP-9, VEGF-D, and HGF than the HFD group. Conclusions: HFD can have a negative impact on the healing process of gastric ulcers in animals by delaying repair in gastric tissue when compared with animals consuming SD.
Keywords: Gastric ulcers; Growth factors; High-fat diet; Matrix metalloproteinases; Obesity